2021
DOI: 10.1021/acs.langmuir.1c01900
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Motifs and Molecular Orientation at the Ionic Liquid/Noble Metal Interface: [C2C1Im][NTf2] on Pt(111)

Abstract: In solid catalysts with ionic liquid layers (SCILLs), ionic liquid (IL) thin films are used to modify the activity and selectivity of catalytic materials. In this work, we investigated the adsorption behavior of the IL 1-ethyl-3-methyl-imidazolium bis(trifluoromethylsulfonyl)imide [C 2 C 1 Im][NTf 2 ] on Pt(111) by combining experimental and theoretical studies. Under ultrahigh vacuum (UHV) conditions, the IL was deposited onto a Pt(111) single crystal surface by physical vapor deposition (PVD) at different su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 75 publications
2
21
0
Order By: Relevance
“…Moreover, evaporated IL films of the very similar IL [C 2 C 1 Im][Tf 2 N] on Pt(111) had already been studied by means of infrared spectroscopy. 26,27 We will compare our results to this study, and provide additional insights also for this system. For our model catalytic approach, we used in situ physical vapor deposition (PVD) to prepare ultra-thin films of [C 1 C 1 Im][Tf 2 N] on Pt(111).…”
Section: Introductionmentioning
confidence: 79%
“…Moreover, evaporated IL films of the very similar IL [C 2 C 1 Im][Tf 2 N] on Pt(111) had already been studied by means of infrared spectroscopy. 26,27 We will compare our results to this study, and provide additional insights also for this system. For our model catalytic approach, we used in situ physical vapor deposition (PVD) to prepare ultra-thin films of [C 1 C 1 Im][Tf 2 N] on Pt(111).…”
Section: Introductionmentioning
confidence: 79%
“…It has been widely reported that IL ions organize in layers near a charged surface. 11−13 Extensive efforts have been made to investigate structural and dynamic properties of ILs near a solid interface as well as the influence of nanoconfinement using spectroscopy, 14,15 X-ray reflectivity, 16 neutron scattering, 17 NMR, 18,19 and electrochemical techniques. 20,21 Nanomechanical methods have provided unique perspectives about the transition of IL behavior upon nanoconfinement toward elastic or solid behavior, which is often referred to as solid-like behavior.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It has been widely reported that IL ions organize in layers near a charged surface. Extensive efforts have been made to investigate structural and dynamic properties of ILs near a solid interface as well as the influence of nanoconfinement using spectroscopy, , X-ray reflectivity, neutron scattering, NMR, , and electrochemical techniques. , Nanomechanical methods have provided unique perspectives about the transition of IL behavior upon nanoconfinement toward elastic or solid behavior, which is often referred to as solid-like behavior. For example, the mechanical impedance of 1-butyl-3-methylimidazolium tetrafluoroborate (abbreviated as [BMIM]­[BF4]) measured under the excitation of a tuning-fork-based atomic force microscope suggested that the interfacial film exhibits a change of properties toward a solid-like phase below a threshold thickness, pointing to capillary freezing or crystallization in confinement.…”
Section: Introductionmentioning
confidence: 99%
“…Note that positive (pointing upwards) and negative (pointing downwards) bands indicate consumed and formed species, respectively. Other bands at 1574 cm −1 ( ν (C=N) ring , ν (C=C) ring ), 1350 cm −1 ( ν as (SO 2 )), 1200 cm −1 ( ν ([NTf 2 ] − )), and 1135 cm −1 ( ν s (SO 2 ), ν as (CF 3 )) we attribute to the supporting electrolyte [C 2 C 1 Im][NTf 2 ] [34] (for details of the ATR‐IR spectrum see Supporting Information) and bands at 2309 cm −1 and 1260 cm −1 to the solvent DCM [32] . Time‐resolved spectra (see Supporting Information Figure S2) show that under our experimental conditions we obtain a quantitative photo‐conversion of the photoswitch in the thin‐layer within a few tenths of a second.…”
Section: Resultsmentioning
confidence: 94%